2019
DOI: 10.1017/s1463423619000495
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ perspectives of providing primary healthcare services to persons with physical disabilities in rural Ghana

Abstract: Background: A growing body of evidence has shown that persons with physical disabilities experience substantial barriers in accessing primary healthcare (PHC) services in rural areas. Negative attitudes from healthcare providers and inaccessible healthcare facilities and equipment are common experiences that negatively affect access to quality healthcare for persons with physical disabilities. However, there is limited research that explores this issue from the perspectives of healthcare providers. This q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 34 publications
7
15
0
9
Order By: Relevance
“…This article forms part of a larger doctoral study designed to understand disability and access to PHC services in rural areas. Some study findings have been reported elsewhere [10,14,15]. However, this article focuses on a dominant theme that emerged from the qualitative data analysis.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…This article forms part of a larger doctoral study designed to understand disability and access to PHC services in rural areas. Some study findings have been reported elsewhere [10,14,15]. However, this article focuses on a dominant theme that emerged from the qualitative data analysis.…”
Section: Methodsmentioning
confidence: 88%
“…Similarly, the government introduced a national health insurance scheme as a health policy to make health care affordable thus increasing access to basic health care for all residents, including those with disabilities [12]. These policies, however, have not been translated into practice as growing evidence suggests that interactions between persons with disabilities and the health care system often culminate in access barriers such as lack of necessary services, financial constraints, inaccessible health care facilities and equipment, and negative attitudes from providers [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revelaram ainda que as unidades foram projetadas sem considerar as necessidades de pessoas que utilizam dispositivos de assistência, como cadeira de rodas. 27 As dificuldades de acessibilidade aos serviços também, são reveladas pela carência de transporte fornecido pelo setor da saúde, que, muitas vezes, é demorado, além da necessidade de Acolhimento na Estratégia Saúde da Família: perspectivas das pessoas com deficiência...| 16 Rev. Enferm.…”
Section: Discussionunclassified
“…Médicos da família expressaram que existe uma incongruência entre a acessibilidade por eles percebida e a real, por não terem a compreensão completa sobre a acessibilidade e sobre as dificuldades das pessoas com deficiência (McMillan et al, 2016). Nesse contexto, os prestadores admitem que a inacessibilidade das instalações e acomodações são barreiras que limitam a prestação de cuidados (Banks et al, 2017;Dassah et al, 2019;McMillan et al, 2016;Mitra et al, 2017;Sonalkar et al, 2020).…”
Section: A -Barreiras Físicasunclassified